O MUSEU DE CIÊNCIAS NATURAIS COMO ESPAÇO EDUCACIONAL - Tissot-Squalli, Mara L.; Hammes, Clara; Araújo, Maria C. P. d.; Cavalheiro, Laísa W.; Correa, Geodeli A. P.; Lima, Jonas D. N. d.; Klein, Fátima R. S.; Coelho, Geraldo C. (Salão do Conhecimento, 2013)
Resumo